Cosmic ray anisotropies from transient extragalactic sources - Harari, Diego Dario (2021)
We study the spectrum and anisotropies of ultrahigh energy cosmic ray transient sources, accounting for the effects of their propagation through the turbulent extragalactic magnetic fields. We consider either bursting sources or sources emitting since a given initial time. We analyze in detail the transition between the diffusive and the quasirectilinear regimes, describing some new features that could be present.